Standardization of indirect regeneration protocol in Lady Rosetta cultivar of potato (Solanum tuberosum) - LAKSHYA SAXENA; POOJA MANCHANDA; MANINDER KAUR; ANU KALIA; SAT PAL SHARMA (The Indian Journal of Agricultural Sciences)
The present experiment was conducted during 2021–22 at School of Agricultural Biotechnology, Punjab Agricultural University, Ludhiana, Punjab to standardize indirect somatic embryogenesis for rapid callus induction, plantlet regeneration and shoot proliferation in the popular potato (Solanum tuberosum L.) cv. Lady Rosetta. Nodal and internodal regions were used as explants for the process under sterilized laminar air flow cabinet conditions. The experiment was laid out in a completely randomized design (CRD) with three replications. About 9.78% callus induction were noticed in the explants cultured on Murashige and Skoog (MS) media supplemented with growth regulators i.e 4.0 mg/L 2, 4-Dichlorophenoxy acetic acid (2,4-D) and 0.5 mg/L Kinetin (Kin) for induction of callus and regeneration of shoot tissues from callus. Simultaneously, 48.9% plantlet regeneration from calli was obtained in the MS media with 4 mg/L Benzyl Amino Purine (BAP) and 1 mg/L Kin. We observed better callus induction at 4.0 mg/L 2,4-D and 0.5 mg/L Kin, shoot induction at 4.0 mg/L BAP and 1.0 mg/L Kin and root induction in half-strength MS media. The regenerated shoots were efficiently grown on rooting media, later transferred for hardening and acclimatized under field conditions. The present study serves as an efficient protocol to conduct tissue culture experiment using potato explants for calli induction, shoot regeneration and rooting in cv. Lady Rosetta. These findings will serve as a significant finding for regenerating potato plants from calli for genetic transformation/genome editing studies.